Cost Comparison of Flexible Pavement on Weak Sub-Grade Soil Modified with Lime and SD - Chaudhary, Braj Kishore; Gautam, Gopal (SCITECH Nepal, 2023)
The effectiveness of flexible pavement is affected by the subgrade quality. The subgrade refers to a compacted layer of soil that provides sideways support to the pavement. When constructed on a weak subgrade, it negatively impacts the pavement's performance, leading to a shorter lifespan. Traditionally, the common method to stabilize a soft subgrade involves removing the weak soil and replacing it with stronger soil. However, due to the high expenses associated with soil replacement, highway agencies are exploring alternative approaches to constructing highways on soft subgrades. Soil stabilization is a commonly employed alternative in pavement construction, serving as an effective method to enhance the engineering characteristics of soil, including its strength and stability. This paper focuses on the utilization of lime and stone dust (SD) as admixtures for an efficient ground improvement technique over weak subgrade soil deposits. The California Bearing Ratio (CBR) test is conducted by making the specimens of weak subgrade by adding the variable percentages of a mixture of lime and SD. First, the soil was mixed up with lime to 12% by weight with an increment of 3% again the soil was mixed with SD with increments of 10% up to 50% by weight of soil. The study determined an optimal lime content of 3% based on the geotechnical properties of the mixture and the cost considerations of lime and the weak subgrade. Following this, SD was added to the optimized lime-weak subgrade mixture in varying increments of 10% by weight, up to a maximum of 40%. The modified mixes were then evaluated for their CBR and maximum dry density values. The CBR is increased to 15% and the total pavement thickness decreased to 725 mm for 50% SD addition with 4.89 % in cost reduction.